Chimeric antigen receptor T-cell therapy targeting a MAGE A4 peptide and HLA-A*02:01 complex for unresectable advanced or recurrent solid cancer: protocol for a multi-institutional phase 1 clinical trial. Issue 11 (14th November 2022) - Okumura, Satoshi; Ishihara, Mikiya; Kiyota, Naomi; Yakushijin, Kimikazu; Takada, Kohichi; Kobayashi, Shinichiro; Ikeda, Hiroaki; Endo, Makoto; Kato, Koji; Kitano, Shigehisa; Matsumine, Akihiko; Nagata, Yasuhiro; et al.
Abstract : Introduction: Adoptive cell transfer of genetically engineered T cells is a promising treatment for malignancies; however, there are few ideal cancer antigens expressed on the cell surface, and the development of chimeric antigen receptor T cells (CAR-T cells) for solid tumour treatment has been slow. CAR-T cells, which recognise major histocompatibility complex and peptide complexes presented on the cell surface, can be used to target not only cell surface antigens but also intracellular antigens. We have developed a CAR-T-cell product that recognises the complex of HLA-A*02:01 and an epitope of the MAGE-A4 antigen equipped with a novel signalling domain of human GITR (investigational product code: MU-MA402C) based on preclinical studies. Methods and analysis: This is a dose-escalation, multi-institutional, phase 1 study to evaluate the tolerability and safety of MU-MA402C for patients with MAGE A4-positive and HLA-A*02:01-positive unresectable advanced or recurrent solid cancer. Two dose cohorts are planned: cohort 1, MU-MA402C 2×10 8 /person; cohort 2, MU-MA402C 2×10 9 /person. Prior to CAR-T-cell infusion, cyclophosphamide (CPA) and fludarabine (FLU) will be administered as preconditioning chemotherapy. Three evaluable subjects per cohort, for a total of 6 subjects (maximum of 12 subjects), will be recruited for this clinical trial. The primary endpoints are safety and tolerability. The severity of each adverse event will be evaluated in accordance with Common Terminology Criteria for Adverse Events V.5.0. The secondary endpoint is efficacy. Antitumour response will be evaluated according to Response Evaluation Criteria in Solid Tumours V.1.1. Ethics and dissemination: This clinical trial will be conducted in accordance with the current version of Good Clinical Practice. The protocol was approved by the Clinical Research Ethics Review Committee of Mie University Hospital (approval number F-2021-017). The trial results will be published in peer-reviewed journals and/or disseminated through international conferences. Trial registration number: jRCT2043210077.